Step-by-Step Minimally Invasive Aortic Valve Replacement: the RAT Approach - Zubarevich,Alina (2021)
Abstract In the growing era of transcatheter aortic valve implantation, it is crucial to develop minimally invasive surgical techniques. These methods enable easier recovery from surgical trauma, especially in elderly and frail patients. Minimally invasive aortic valve replacement (MIAVR) is frequently performed via upper hemisternotomy. We describe MIAVR via right anterior thoracotomy, which is associated with less trauma, rapid mobilization, lower blood transfusion rates, and lower risk of postoperative wound infections. As minimally invasive procedures tend to take longer operative times, we suggest using rapid-deployment valve prostheses to overcome this limitation. This description focuses on the technical aspects and preoperative assessment.